(untitled) - Burton-Roberts, Noel (New York, 2016)
This highly successful text has long been considered the standard introduction to the practical analysis of English sentence structure. It covers key concepts such as constituency, category and functions, and also utilises tree diagrams throughout to help the reader visualise the structure of sentences.
Cú pháp học
Keywords: Tiếng Anh,English language; Cú pháp,Syntax